Respuesta :

Answer:

4at

Step-by-step explanation:

1. Distribute. You well get at+4a-4a+3at.

2. Eliminate the opposites (+4a and -4a cancel out to equal 0, which can then be excluded from the equation). You will get at+3at.

3. Add. at+3at=4at

Answer:

Step-by-step explanation:

Use distributive property

a(t+4) - a(4 - 3t) = a*t + a*4 +(- a) * 4 - (-a)*3t

                       = at+ 4a - 4a + 3at    {combine like terms}

                       = at + 3at + 4a - 4a   {add /subtract like terms}

                       = 4at  

ACCESS MORE